2020
DOI: 10.1016/j.enpol.2020.111461
|View full text |Cite
|
Sign up to set email alerts
|

Net solar generation potential from urban rooftops in Los Angeles

Abstract: Rooftops provide accessible locations for solar energy installations. While rooftop solar arrays can offset inbuilding electricity needs, they may also stress electric grid operations. Here we present an analysis of net electricity generation potential from distributed rooftop solar in Los Angeles. We integrate spatial and temporal data for property-level electricity demands, rooftop solar generation potential, and grid capacity constraints to estimate the potential for solar to meet on-site demands and supply… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Utilities, fossil fuel purveyors, and other groups with vested interests in minimizing disruption of the status quo, support a market-driven approach where decentralization is limited, the extent of DER adoption is greatest among higher-income cohorts, and where DERs serve to mitigate grid vulnerabilities by slowing the growth in demand for gridsupplied energy in certain locations (Porse et al, 2020;Brockway et al, 2021). Under this market-based adoption paradigm, DER functions primarily as a means to slow the growth in energy consumption among the most prolific users and to defer grid upgrades and operational changes.…”
Section: Energy Democracy and Decentralizationmentioning
confidence: 99%
“…Utilities, fossil fuel purveyors, and other groups with vested interests in minimizing disruption of the status quo, support a market-driven approach where decentralization is limited, the extent of DER adoption is greatest among higher-income cohorts, and where DERs serve to mitigate grid vulnerabilities by slowing the growth in demand for gridsupplied energy in certain locations (Porse et al, 2020;Brockway et al, 2021). Under this market-based adoption paradigm, DER functions primarily as a means to slow the growth in energy consumption among the most prolific users and to defer grid upgrades and operational changes.…”
Section: Energy Democracy and Decentralizationmentioning
confidence: 99%
“…Currently, many Indonesian households do not use solar panels to generate electricity. Therefore, there is significant potential for installing rooftop solar panels not only in big cities but also in the rural areas of Indonesia, which do not get stable electricity [3]. It reports that countries such as Switzerland have a high potential for rooftop solar panel power generation [4].…”
Section: Literature Reviewmentioning
confidence: 99%
“…We found that under-resourced communities in Los Angeles generally have greater potential to contribute peak solar generation exports to the electric grid, along with greater excess capacity in local circuits to accept solar from sources other than rooftops (Porse et al 2020 ). This means that solar capacity potential is underutilized in situ, pushing purchases of solar to off-site solar arrays, taking up lands that could be used for other purposes.…”
Section: Insights From Data-driven Researchmentioning
confidence: 99%